ገበታ: የአየር ለውጥን መቋቋም ስለሚችሉ የተሻሻሉ የእንስሳት መኖ ቴክኖሎጂዎች የራዲዮ ፕሮግራም፡ ክፍል ሁለት - International Livestock Research Institute (International Livestock Research Institute, 2025)
This second broadcast from Debre Birhan on Fana FM 90.0 examines the significant contribution of Ethiopia's livestock sector to the national economy, with emphasis on feed and forage value chains including production, quality and utilization. The episode highlights the benefits of cultivated forages in the North Shewa zone, current levels of farmer awareness, and outlines strategies for the sustainable intensification of livestock production systems.